Active Methodologies to Achieve Comprehension [Metodologías Activas Para Alcanzar el Comprender] - Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2017)
The article shows the results of methodological intervention of the type active and cooperative through the use of robotic technology. The objective of the study was to demonstrate that n-dimensional interventions develop understanding over doing, allowing meaningful learning. This technology is not used only as a motivating and entertaining element; its use plays a leading role within the class and becomes an instrument of the teaching-learning process. The samples correspond to two courses, in two consecutive semesters, of similar population size, similar age group, and similar gender distribution. The variables defined, recorded, and analyzed are understanding and dispersion in the classroom. The results were significant, thus establishing the importance of achieving the "doing" through the unavoidable path of comprehension.
Keywords: Comprehension; Dispersion; Robotics; Teaching-learning process